Shabanu, daughter of the wind. - Staples, Suzanne F. (New York Alfred A. Knoph,Inc., 1989)
Life is both sweet and cruel to strong-willed young Shabanu, whose home is the windswept Cholistan Desert of Pakistan. The second daughter in a family with no sons, she$1 (Bs been allowed freedoms forbidden to most Muslim girls. But when a tragic encounter with a wealthy and powerful landowner ruins the marriage plans of her older sister, Shabanu is called upon to sacrifice everything she$1 (Bs dreamed of. Should she do what is necessary to uphold her family$1 (Bs honor$1 (Bor listen to the stirrings of her own heart?s
Keywords: Fiction